Forcing lettuce - Painter, Joseph W. (My University, 1907)
Introduction: In the last few years, forcing lettuce for winter use, has become a very profitable business in different parts of the country. To be successful, the forcing houses must be located close to a good and steady market. A city of 10,000 ought to demand sufficient lettuce to support a fair sized lettuce business. A town of half that size makes a combined forcing and greenhouse business very profitable. The sale of lettuce is not necessarily confined to the home market as it can be shipped to very good advantage. For long shipments it is usually placed in barrels, the cabbage headed varieties stem up, while the open bunch is placed on its side. In warm weather the packed lettuce must be ventilated, while in cold weather the barrels or boxes should be lined with paper. The season for forced lettuce north of the 35 parallel, extends from October to April or even to May. This extends over the greater part of the year, and gives plenty of time to raise three crops. The forcing house does not need to stand idle during the spring and summer, as other things may be grown, such as tomatoes, cucumbers, celery, onions, cabbage, etc. Various things cat in this way be started and disposed of to small gardeners for early gardens. Lettuce may be grown without much trouble if it is carried on in the proper manner. There are several points to be considered, some rather small but nevertheless quite important.
Citation: Painter, Joseph W. Forcing lettuce. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Lettuce; Lettuce Growing; Agriculture Techniques; Theses